PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMP N 1 BASO TAHUN PELAJARAN 2016/2017 - Yenti, Fepryna (Menara Ilmu, 2017)
This research began with the lowness of students' mathematical communication skills, one of which is caused by pembelajaaran which remains centered on the teacher. One effort to overcome the problem is to apply the model of contextual learning. This study aims to determine the mathematical communication skills of students who take the learning with contextual learning model is better than the students who take the conventional learning models in class VIII SMP Negeri 1 Baso. This type of research is experimental research design that Randomized Control Only Design. The population in this study was grade VIII1, VIII2, VIII3, VIII3, VIII4, VIII5 SMP Negeri 1 Baso in academic year 2016/2017. Sampling was done by using Random Sampling. Class VIII1 an experimental class and class VIII4 a control class. Instrument of research is mathematical communication ability test. Analysis of the data used is the t test. Hypothesis test results obtained and with and df = 43, so. Based on the criteria for means test reject H0 and it can be concluded that the mathematical communication skills students learn by using contextual learning model is better than learning by using conventional learning models. Keyword : Model of contextual learning, students' mathematical communication skills